A profile of the skills, attributes, development, and employment opportunities for sport scientists in Australia - Bruce, L.; Bellesini, K.; Aisbett, B.; Drinkwater, E. J.; Kremer, P. (Journal of Science and Medicine in Sport, 2022)
Objectives: The purpose of this study was to document the technical and transferrable skills required for sport scientists, and perceived employment opportunities both currently and in the future with a particular emphasis on comparisons between academic and applied sport scientists. Design: Cross-sectional survey methodology. Methods: 117 Australian sport science employees completed an online survey capturing demographic information, perceptions about the importance of technical skills, transferable skills, future employment opportunities as well as free-text information on future careers, challenges, and opportunities for the profession. Descriptive statistics were used to summarise information and comparisons made between academic and applied sport science participants. Results: Participants were predominantly male and 35 years or younger, with half reporting they held only one position within the industry. Most technical and transferrable skills were rated as important (>4.0 out of 5.0), with practitioner-focused skills rated somewhat more important by applied sport scientists compared to scientific-focused skills rated somewhat more important by academics, and applied sport scientists generally rating transferable skills as more important compared to academics (d > 0.5). Value and supply/demand were identified as challenges to the industry with discipline-specific roles and non-elite populations considered areas for future jobs. Conclusions: Participants felt there would be more jobs in the future and that these would be in discipline-specific roles and/or non-elite populations. Both technical and interpersonal skills were considered important for sport scientists. The greatest challenges are how sport science is valued and the potential oversupply of sport science graduates.